RISK PERCEPTION AND PREVENTION IN A HEALTH EMERGENCY CONTEXT: CASE INFLUENZA A (H1N1), 2009 - Carro Pérez, Ennio Héctor (Universidad Autónoma de Tamaulipas, 2016)
The study of risk perception and its relation with the use of prevention strategies can provide information on how preventive behavior works in situations of imminent danger. The objective of the present study was to know the evaluation made by residents of the southern area of Tamaulipas, Mexico, on the risk of being affected by the influenza virus A H1N1 and the prevention measures they adopted during the months of April to May 2009. The sample consisted of 60 volunteers who responded to a mixed questionnaire and risk perception scale through e-mail. The most frequent prevention measures were: avoidance of public places (69.5%), absence from work or school (68.3%), and use of mouth cover (40%). On the other hand, it was observed that those who decided to follow one of the preventive measures recommended by the health institutions evaluated as more dangerous and contagious the A H1N1 influenza than those who did not (p <.05).